Mitigasi risiko komprehensif di perbankan syariah: Studi kasus pengelolaan risiko yang terintegrasi - Sholahudin, Aris Athoillah (Maliki Interdisciplinary Journal, 2024)
Risk in banking is something that a bank should avoid. Risk cannot be predicted, risk can only be anticipated. The aim of this research is to describe the mitigation carried out by Bank ADN Syariah towards its risks as a banking company. Case studies are used, and the data used is secondary data. This analysis shows that the risks faced by Bank ADN Syariah are organized and the company’s system for identifying and managing all risks is mature.